PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS DISCOVERY LEARNING MENGGUNAKAN PETA DIGITAL GUNA MENINGKATKAN LITERASI GEOSPASIAL SISWA KELAS IV SEKOLAH DASAR - Novianti, Tiara; Meizatri, Ranti; Amini, Risda; Fitri, Ummiatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study focused on developing a Discovery Learning-based instructional medium utilizing digital maps to enhance the geospatial literacy of fourth-grade elementary school students in IPAS learning, particularly on map-related topics. The study adopted a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The resulting product, GeoExplore, was created through Google Sites and integrated with Google Earth exploration, instructional materials, teacher guidance, and student worksheets. The developed medium underwent validation by material, language, and media experts and was implemented in four elementary schools to assess its practicality. The validation results indicated scores of 95% for material, 80% for language, and 95% for media, resulting in an overall average of 90%, which was classified as very valid. The practicality assessment also demonstrated positive responses from both teachers and students across the four schools. Furthermore, effectiveness was examined through pretest and posttest scores, with the N-Gain results indicating a high category for the schools with complete effectiveness data. Therefore, GeoExplore was considered valid and practical and showed potential to support the development of students' geospatial literacy through digital map exploration.